The Influence of Product Innovation and Digital Marketing on the Ompetitiveness of MSMEs - Laras Dwi Yanti; Ida Ayu Made Er Meytha Gayatri; Wagini Wagini (Utami Publisher, 2026)
This study aims to determine the effect of product innovation and digital marketing on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Kota Manna. This research uses a quantitative method with an associative approach. The population in this study consisted of 620 MSME actors in Kota Manna, with a sample of 86 respondents determined using the Slovin formula. Date were collected through questionnaires using a likert scale and analyzed using multiple linear regression analysis. The data analysis techniques included validity test, reliability test, coefficient of determination (R2), t-test, (partial), and F-test (simultaneous) using SPSS version 21. The result of this study indicate that product innovation has a positive and significant effect on MSME competitiveness with a significance value of 0,000<0,05. Digital marketing also has a positive and significant effect on MSME competitiveness with a significance value of 0,001<0,05. Simultaneously,product innovation and digital marketing significantly affect MSME competitiveness with an F-count value of 988.509 greater than F-table 3.108. The coefficient of determination (R2) shows a value of 0,767, meaning that 76,7% of MSME competitiveness can be explained by product innovation and digital marketing, while the remaining 23,3% is influenced by other variables outside this research model.